Perbandingan Volatilitas Harga Global dengan Harga Domestik Crude Palm Oil (CPO) Indonesia - Sopia Azida (Universitas Batanghari Jambi, 2026)
This study aims to analyze global Crude Palm Oil (CPO) price movement trends and domestic Indonesian CPO prices, compare their volatility levels, and analyze the influence of global CPO prices on domestic Indonesian CPO prices during the period 2017–2024. The analysis methods used include descriptive analysis thru the calculation of annual returns, standard deviation, and coefficient of variation to measure price volatility, as well as simple linear regression analysis to determine the influence of global CPO prices on domestic CPO prices. The research findings indicate that global and domestic CPO prices experienced significant fluctuations during the study period, with peak prices occurring in 2021–2022 and a sharp correction in 2023. The volatility level of domestic CPO prices is higher than that of global CPO prices, indicating that the domestic market is more sensitive to changes in government policy and domestic supply conditions. The results of simple linear regression show that global CPO prices have a positive and significant effect on domestic CPO prices in Indonesia, with a regression coefficient of 1.35 and a coefficient of determination (R²) value of 0.779. This indicates that most of the variation in domestic CPO prices can be explained by changes in global CPO prices, although internal factors such as trade policies and biodiesel programs also strengthen the domestic price response..